Proses Keputusan Pembelian Konsumen Terhadap Daging Ayam Broiler di Pasar Tradisional Kiaracondong dan Griya Kiaracondong - Adrian, Samuel; Saidah, Zumi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The purchasing decision process is a consumer decision in prioritizing products that are in various sets of choices. This research uses a case study at Kiaracondong Traditional Market and Griya Kiaracondong. The purpose of this study was to determine the characteristics of consumers of broiler chicken, the decision process of broiler meat and the relationship between the characteristics of consumers of broiler chicken and the process of purchasing broiler chicken meat by using descriptive analysis method and Chi-Square analysis. Based on the characteristics of consumers purchasing chicken meat, there are differences in the distribution of age, marital status and number of family members, where respondents to traditional kiaracondong markets tend to be older and more are married. Meanwhile, based on the purchasing decision process, the difference lies in information search, evaluation of alternatives and post-purchase. On the relationship between consumer characteristics and the buying decision process, age groups and activities where the Pearson chi-square value is smaller than alpha.